Kesalahan Penerjemahan Bahasa Mandarin pada Mahasiswa Sastra China Binus University pada Mata Kuliah Terjemahan Umum - Agustinus Sufianto (Humaniora, 2010)
Translation is an activity that transforms a written or verbal language to other written or verbal language. In its process, a translator should  overcome the difficulty that caused by the cultural differences, habits, vocabularies and grammars which could help the translator  to translate precisely without changing the original meaning of  translation’s source. Through the translation lesson, the writer found some factors that caused the student’s mistake in translating Chinese into Indonesian or Indonesian into Chinese. On the other side, The writer found that the translation’s mistakes are caused by the lack of understanding Chinese and Indonesian‘s history, culture and habit. There are some factors that lead to the lack of understanding of Chinese history, culture and habit such as the inability of student  to understand the meaning of  history, culture and habit that usually are contained on the words, proverb and sentences, the environment that are not supporting students to have a deep understanding of Chinese history, culture and habit. The deeper understanding of Chinese culture, history and habits could help student to translate Chinese that influenced by history, culture and the habit of Chinese precisely. Through the observation, the writer will analyze some factors and analyze how the lecturers could overcome the difficulties of translation that are faced by students.